Phosphoglucomutase‐1 deficiency: Intrafamilial clinical variability and common secondary adrenal insufficiency. (19th August 2015) - Loewenthal, Neta; Haim, Alon; Parvari, Ruti; Hershkovitz, Eli
Abstract : Phosphoglucomutase 1 (PGM1, EC 5.4.2.2) plays a critical role in glucose homeostasis and is also essential for protein N‐glycosylation. The main clinical manifestations of PGM1 deficiency (MIM 614921) reported in 19 patients from different ethnic backgrounds include the following: cleft uvula/palate, Pierre Robin sequence, muscle weakness, dilated cardiomyopathy, growth retardation, elevated serum transaminases, hypoglycemia, and various endocrine abnormalities. We report the variable clinical picture of seven patients with PGM1 deficiency from a consanguineous family. Medical records of the patients were reviewed for clinical details and endocrine evaluation. Whole exome sequencing (WES) was performed. Seven patients aged 2–29 years were included, one patient died at 13 years old when getting off the school bus. All patients have an abnormal palatine structure (cleft palate, bifid uvula) and elevated serum transaminases, 4/7 have short stature (<−2 SDS) and one was diagnosed with growth hormone deficiency. Recurrent episodes of ketotic hypoglycemia were present in 6/7 patients. In two patients, hypoglycemic episodes have spontaneously resolved later on. Four out of seven patients have deteriorating adrenal function with abnormally low cortisol and ACTH levels during hypoglycemia and subnormal response of cortisol to low dose ACTH test . Serum electrolytes were within normal range. Hydrocortisone replacement therapy improved, but not entirely eliminated hypoglycemic episodes. WES revealed a previously described homozygous mutation c.112A>T, p.Asn38Tyr in the PGM1 gene. The clinical picture of PGM1 deficiency is variable among patients with the same mutation and genetic background. ACTH deficiency should be considered in any PGM1 deficient patient with hypoglycemia. © 2015 Wiley Periodicals, Inc.